Response Surface Methodology (RSM) and electromagnetic optimization of pigment production by Sporobolomyces sp S5 and Rhodotorula sp A21 in submerged fermentation - Garuba, Emmanuel O.; Ajunwa , Obinna M.; Olaifa, Kayode W.; Onilude, Abiodun A. (Journal of BioScience and Biotechnology, 2020)
This study aimed at enhancing pigment production by Sporobolomyces sp S5 and Rhodotorula sp A21 in submerged fermentation using statistical method and electromagnetic inducement technique. One-factor-at-a-time (OFAT) experiments were initially employed to screen cultural and physical parameters that significantly affect pigment production in both cultures. The most significant medium components and physical factors were selected using Plackett-Burman (PB) experiment design while a Central Composite design (CCD) of the response surface methodology (RSM) was used to determine the optimal levels and the interactive effects among the selected components. Results of OFAT experiments suggested that glucose, yeast extract, calcium sulphate and sodium nitrate, incubation temperature of 30 °C, incubation period of 72 hours and, pH 6.5 and 7.0 for Sporobolomyces sp S5 and Rhodotorula sp A21 respectively were best for pigment production. The results of the Plackett-Burman (PB) design showed that yeasts extract incubation temperature significantly affected Pigment production by Rhodotorula sp A21 while glucose, incubation time and pH affected pigment yield in Sporobolomyces sp S5 cultures RSM optimization revealed maximum pigment yield of 170.34±0.02 µg/mL (Sporobolomyces sp S5) and 242.48±0.02 µg/mL (Rhodotorula sp A21) when the optimal levels and the interactive effects among the selected factors were investigated. Exposure to electromagnetic filed (EMF) further enhanced pigment production with a pigment yield of 202.70±0.02 µg/mL by Sporobolomyces sp S5 at 40 minutes exposure under statistically optimized conditions.